Experimental investigations on nanotechnology in the health field (Research, Society and Development, 2024)
“Nanotechnology” has attracted attention in recent years, considering that this science leads to an increase in the quality of life of human beings and the conservation of the environment. This investigation aims to describe the evidence regarding the usefulness of the social body through nanotechnology and its application in medicine since its practical impact is increasingly accepted. This is exploratory and qualitative research through scientific articles, magazines, books, newspapers, theses and dissertations, in the databases Google Scholar, PubMed, Scientific Electronic Library Online (Scielo), Semantic Scholar, Academy of Science and Technology, Virtual Health Library (BVS periodicals) published between 2008 and 2020. Based on the design of this inquiry, it was possible to observe that nanotechnology enables advantages in the field of living beings' wisdom, not merely in the medical environment, since it is materialized through drugs, natural or synthetic substances for human hygiene, manufacturing, and equipment, among others. It is concluded that the purpose of this research was achieved, since it was possible to report methods implemented with nanotechnology given the information described here, as advantages in the face of diseases that affect the various continents.